Application of Nusa and Rara Audio Visual Media in Planting Religious Character of Children in Group B Aba KindergartenTirtajaya - Amik, Zakiah Magfiratul; Rahayu, Meggi; Idris, Mustamin; Ayuningtias, Fitriani; Salam, Abdul (Yayasan Sinergi Kawula Muda, 2025)
The problem in this research is how to instill religious character in group B1 children through the animated audio visual media Nussa and Rara. This research is Classroom Action Research (PTK) which applies audio-visual media in cultivating children's religious character. Subject this research is child group B1 TK ABA Tirtajaya Regency Banggai Which amounted to 10 child, 5 man And 5 Woman. Study This done in two cycle Which each consists from two meeting session. Activity learning consists from four level that is planning, implementation activity, observation And reflection. Method collection data through interview, sheet observation And documentation. After that, data analyzed with method descriptive-qualitative And descriptive-quantitative. At the pre-action stage, the percentage of classical completeness obtained was 10% or consisted of 1 child who was included in the BSB (Very Well Developed) category and as many as 9 children did not meet these criteria. Furthermore, the classical completeness percentage was obtained at 30% or 3 children in the BSB (Very Well Developed) category and 7 children had not met these criteria in the first cycle of action, meeting I, then the researcher carried out the first cycle of meeting II and obtained classical completeness of 50%, which means they did not meet the standard of classical learning completeness set at 75% and caused the researcher to continue the research action to the next cycle. In the second cycle of the first meeting, the researchers found that there were 7 children included in the BSB (Very Well Developing) category with a percentage of classical completion obtained of 70%, while in the second cycle of the second meeting the researchers found 9 children included in the BSB (Very Well Developing) category and 1 child in the BSH (Developing According to Expectations) category. It can be concluded that the application of audio visual media can instill religious character in the children of group B1 TK ABA Tiertajaya, Banggai Regency.